Modelling rainwater harvesting for commercial buildings - Foo, Swee Wen; Mah, D.Y.S.; Emily, Ayub Bartholomew (IWA, 2017)
Commercial areas are generally fully paved and with more impervious land cover than residential areas. This paper demonstrates a wall-mounted rainwater harvesting system designed to deal with limited land space. An arrangement of three tanks in series was used on a commercial shop lot where flat roofs generate large amounts of runoff. The system is compact, and can be installed and fitted close to any wall, promoting the efficient use of space. Analytical procedures and computational fluid dynamic modelling were used to explore the system’s potential. This rainwater harvesting system, with its three water storage tanks, works well, and is suitable for implementation and can be integrated into urban stormwater management.